INTEGRALO: Digital English Learning with Local Values to Foster Inclusive Economy in Padengo Village: Pengabdian - Haris Danial; Indri Wirahmi Bay; Muhammad Rezky Friesta Payu; Yulinda L. Ismail; Sri Widyarti Ali (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Padengo Village in West Limboto District, Gorontalo Regency, is rich in natural resources and cultural heritage, but faces challenges in human resource development. Most residents work in the agriculture and livestock sectors with low levels of education, with many having only completed primary education or no schooling at all. To address this issue, the INTEGRALO (Internalization of Local Values) program was introduced, combining digital-based English learning with local wisdom to improve language skills and strengthen cultural identity. This program encourages active community participation by utilizing technology to make learning more engaging and contextual. As a result, residents are able to process corn into chips with simple packaging, compile a Local Wisdom Pocket Book as a cultural archive, and manage a village website, which is now run by youth and officials after training. In the area of ​​social education, teenagers learned about the dangers of early marriage, while children learned about bullying. Student involvement also strengthened academic relationships with the community. Overall, the Thematic KKN II Program has had a tangible impact on Padengo Village, from improving the local economy, cultural preservation, digital literacy, and educating the younger generation.